FoxP3+ regulatory T cells in oral tongue squamous cell carcinoma in young and older patients - Marina Gonçalves do AMARAL; Luana Samara Balduíno de SENA; Aline Carvalho BATISTA; Elismauro Francisco MENDONÇA; Manuel Antônio GORDÓN-NÚÑEZ; Pollianna Muniz ALVES; Cassiano Francisco Weege NONAKA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Regulatory T (Treg) cells can suppress antitumor immune response, but little is known about possible age-related differences in the number of these cells in the microenvironment of oral tongue squamous cell carcinoma (OTSCC). The aim of this study was to determine the number of FoxP3+ Treg cells in the microenvironment of OTSCC in young (≤ 45 years) and older (≥ 60 years) patients, and to correlate the findings with clinicopathological parameters (sex, tumor size/extent, regional lymph node metastasis, clinical staging, and histopathological grade of malignancy). Forty-eight OTSCCs (24 diagnosed in young patients and 24 diagnosed in older patients) were selected. Lymphocytes exhibiting nuclear immunopositivity for FoxP3 were quantified at the tumor invasive front and the results were analyzed statistically using the non-parametric Mann-Whitney test. FoxP3+ lymphocytes were observed in all cases assessed. The number of FoxP3+ lymphocytes in OTSCC tended to be higher in older patients (p = 0.055). Analysis of OTSCC in males and in early clinical stages revealed a higher number of Treg cells in older patients than in young ones (p < 0.05). In older patients, the number of Treg cells tended to be higher in smaller tumors (p = 0.079). Tumors with intense inflammatory infiltrate exhibited a larger number of Treg cells, both in young (p = 0.099) and older patients (p = 0.005). The results suggest a greater participation of Treg cells in immunoinflammatory responses in the microenvironment of OTSCC in older patients, particularly in males and in early stages.